Relationship Between Parenting Styles and Mental Health in Adolescent - Anggawi, Angel Honey; Silitonga, Hanna Tabita Hasianna; Tandoyo, Eric Dino; Tantana, Olivia; Adrianto, Hebert (Faculty of Medicine, Universitas Airlangga, 2025)
Introductions: Many things could affect mental health, especially for adolescents as they are at the age susceptible to many things. One of the things that could affect mental health is parenting styles. Objective: To analyze the relationship between parenting styles and adolescent mental health. Methods: The method used in this research was observational analytics with a cross-sectional design. The instruments used for this study were Parental Authority Questionnaire-Short (PAQ-S) and Depression, Anxiety, Stress Scale-21 (DASS-21). A total of 197 samples were taken from a school in Surabaya. The hypothesis was tested using Kruskal-Wallis and Mann-Whitney on SPSS. Results: Of 197 respondents, 81.2%, 18.3%, and 0.5% were categorized into the authoritative, authoritarian, and permissive parenting styles respectively. It has been found that only 3% of 197 have good mental health. The Kruskal-Wallis test showed that parenting styles affect adolescent mental health with a p-value of less than 0.05. Meanwhile, the Mann-Whitney test showed a difference between the effect of authoritative and authoritarian parenting styles with a p-value of less than 0.05. In contrast, authoritative and authoritarian parenting styles were found to have no significant difference in the outcome with the permissive category with a p-value higher than 0.05. Conclusion: The prevalence of mental health disorders in adolescents at School X Surabaya was found to be 97% and is affected by different types of parenting styles. Authoritative and authoritarian parenting styles produced significantly different outcomes, while the permissive doesn't show as much due to a limited sample.